2001
DOI: 10.1111/j.1469-445x.2001.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracing functionally identified neurones in a multisynaptic pathway in the hamster and rat using herpes simplex virus expressing green fluorescent protein

Abstract: Using a genetically modified herpes simplex virus encoding green fluorescent protein we sought to establish if this viral modification could be used in transneuronal tracing studies of the sympathetic nervous system. The herpes simplex virus encoding green fluorescent protein was injected into the adrenal medulla of three hamsters and six rats. After a suitable survival period, neurones in the sympathetic intermediolateral cell column of the thoracolumbar spinal cord, rostra1 ventral medulla and paraventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…2 Blue: Saper et al, 1976;Hosoya, 1980;Strack et al, 1989a,b;Ranson et al, 1998;Motawei et al, 1999). Furthermore, SPNs provide the final site at which major integration within the central nervous system (CNS) occurs, and represent a common pathway for output from the CNS to the periphery as sympathetic nerves that innervate the heart, blood vessels and adrenal medulla (Strack et al, 1989a,b;Pyner et al, 2001). Descending PVN projections within the IML have numerous sites of close apposition with the soma and dendrites of adrenal-medullary, stellate ganglion and superior cervical projecting SPNs (Hosoya et al, 1995;Ranson et al, 1998;Motawei et al, 1999).…”
Section: Organisation Of the Pvnmentioning
confidence: 97%
See 1 more Smart Citation
“…2 Blue: Saper et al, 1976;Hosoya, 1980;Strack et al, 1989a,b;Ranson et al, 1998;Motawei et al, 1999). Furthermore, SPNs provide the final site at which major integration within the central nervous system (CNS) occurs, and represent a common pathway for output from the CNS to the periphery as sympathetic nerves that innervate the heart, blood vessels and adrenal medulla (Strack et al, 1989a,b;Pyner et al, 2001). Descending PVN projections within the IML have numerous sites of close apposition with the soma and dendrites of adrenal-medullary, stellate ganglion and superior cervical projecting SPNs (Hosoya et al, 1995;Ranson et al, 1998;Motawei et al, 1999).…”
Section: Organisation Of the Pvnmentioning
confidence: 97%
“…We can assume it is a parvocellular (presympathetic) neurone and/or a GABAergic interneurone because viral tracing studies have shown the presence of presympathetic neurones in the dorsal cap and lateral parvocellular regions of the PVN. The axons of these neurones project to different end organs and sympathetic ganglia including the adrenal medulla, kidney and superior cervical ganglion (Strack et al, 1989a,b;Schramm et al, 1993;Huang and Weiss, 1999;Jansen et al, 1995;Pyner et al, 2001;Huang et al, 2002) with GABAergic interneurones surrounding these regions (Watkins et al, 2009).…”
Section: Organisation Of the Pvnmentioning
confidence: 98%
“…Recombinant fluorescent viruses have been generated for other viruses to investigate the movement of viral particles inside the infected cell [16]–[21]. For HCMV several studies have been published showing ectopic expression of the green fluorescent protein [22]–[24].…”
Section: Introductionmentioning
confidence: 99%
“…At least the dynamic aspects of interactions between virus particles and target cells are best studied in live-imaging approaches that have been enabled by the development of green fluorescent virus variants. Recombinant fluorescent viruses have been reported for herpes simplex virus and pseudorabies virus, the live imaging of which provided new insights into the nature of particle movements within relevant target cells (4,6,12,21,22,27). Green fluorescent cytomegalovirus has also been reported (8,10,11,16,20,23,30); however, to date only nonstructural proteins have been tagged, and therefore these variants did not produce green fluorescent progeny virions.…”
mentioning
confidence: 99%